Dor crônica e desempenho cognitivo em idosos cuidadores - Terassi, Marielli (2019)
In recent years, an increasing number of elderly people who care for another elderly person in the same household have been observed. This elderly person may be more susceptible to increased stress, overload and chronic pain. Pain can negatively influence social, psychological and cognitive variables, and some studies describe a worse cognitive performance in individuals with chronic pain, but the studies in the literature are still controversial. Thus, this thesis aimed to: 1) Compare the performance and cognitive processing of elderly caregivers and non-caregivers with and without chronic pain. 2) Verify the relationship of cognitive performance and chronic pain over time in elderly caregivers and the factors associated with this cognitive decline. In order to achieve the objectives, two studies were performed. In the first study, a cross-sectional study was conducted with 149 elderly individuals divided into four groups matched for gender, age and education. The groups were divided into: elderly caregivers with chronic pain, elderly caregivers with absence of pain, elderly caregivers with chronic pain and elderly caregivers with absence of pain. In order to verify the intensity of the pain, the numerical scale of pain was used and for the evaluation of cognition the Brief Cognitive Screening Battery (BRRC), the Addenbrooke's Cognitive Examination (ACE_R) and the cognitive processing through the evoked potential (P300). Significant statistical differences between participants with and without chronic pain were found in the attention / orientation domains, visuospatial abilities and total score of the ACER instrument. In the BBRC the differences were found in the painless group between caregivers and non-caregivers, with better results in the caregiver group. There was no effect between subjects or interaction (care and pain) on P300 amplitude and latency. The second article was a longitudinal study, conducted with 104 elderly caregivers between the years 2014 and 2018. Participants were divided into two groups: with chronic pain and absence of pain. All comparisons were adjusted for gender, age, number of medications, number of comorbidities, hours of care, depression and stress. For data analysis, a mixed linear model and ANCOVA with a significance level of 5% were used. Cognitive decline was observed over four years in the elderly with chronic pain in the memory domains (p = <0.01; 95% CI = 0.75-2.84) and in the total score of the ACE-R instrument (p = 0.02; 95% CI = 0.32-4.25) in relation to the elderly without pain, however, no associated factor was identified in this decline. Despite intragroup changes, there was no evidence that the pain group achieved a significant change from the pain-free group. Regarding the group with chronic pain, it was not possible to verify an association between pain intensity and cognitive performance. In conclusion, the results showed that the elderly caregivers with chronic pain presented worse cognitive performance over four years in the total score of the ACER instrument and in the memory domain, but there was no difference between groups in cognitive performance.